ABOUT THE POSSIBILITY OF THE METAL OF CORD QUALITY PRODUCTION WITHOUT USING OF VACUUMATOR ON THE FIRST LINE OF RUP “BMZ” - S. V. Kazakov; V. Ju. Gunenkov; I. V. Kushnerev; P. V. Bizukov; V. A. Matochkin; N. V. Andrianov (Литьë и металлургия)
The new approach to the description of the nonmetallics elimination process in the process of the out-of -furnace processing using hydrodynamic and physical-chemical models is offered. The possibility of control of the nonmetallics elimination process in the course of processing at the installation *furnace-bowl” is shown.